Eksplorasi Budaya “Bapa’ Babu’ Guru Rato” dalam Menciptakan Kebersyukuran Siswa kepada Orang Tua - Azizatul Karimah; Mohammad Mahpur; Yulia Solichatun (Jurnal Psikologi Islam dan Budaya, 2022)
Gratitude is one of the concepts in Positive Psychology, which is the field of psychology that views life from a positive perspective. The cultural heritage of "Bapa 'Babu' Guru Rato" in the Madurese ethnicity which places parents as the first people who must be glorified and respected. This value could shape the positive character of students to have a high level of gratitude to their parents. This study aims to explore how students' gratitude for parents in Madura is manifested. This study used a qualitative method, which involved 4 junior high school students in Sumenep with different family backgrounds as subjects. The results of observations and interviews show that there is an internalization of the cultural values of “Bapa' Babu' Guru Rato”. This internalization is strengthened by the existence of hope, modeling, attachment, and empathy that are formed between students and parents so that they can form students' gratitude to their parents as students get from the environment.